The Morphological Analysis of Derivational Affixation on The Heroes’ Quotes in Mobile Legends:Bang Bang - Verencia Mercy -; Riris Mutiara Paulina (Fakultas Sosial dan Humaniora - Universitas Buddhi Dharma, 2021)
To understand the meaning within the word is necessary in order to comprehend the context of text. Hence, this research is disscussed about derivational affixes found in the online game, because the meaning within the words are studied in derivational affixes. It was specifically focused on identifying the types of derivational affixes on the heroes' quotes in Mobile Legends: Bang Bang. This research utilizes Bauer's (1983) and Fromkin‟s (2007) theory. The data was gathered from the heroes' quotes in Mobile Legends: Bang Bang. OALD and OLAG are used to find the meaning of each word. The discovery indicated that there are 63 words that contain derivational affixes and categorized as class-maintaining derivation or class-changing derivation. 40 words shows class-changing derivation including noun derivations (22 words) with affixes such as – ce, -er, -ness, -ure, -ence, -ion, -ation, -al, -ment, -dom, -ity, and –ster. Verb derivations (2 words) with affixes such as be- and em-. Adjective derivations (11 words) with affixes such as –y, -ful, -tant, -al, -en, and –ic. Adverb derivational (5 words) with affixes such as a-, -ly and –y. 23 words shows class-maintaining derivation including noun (13 words) with affixes such as in-, -y, -ner, -ness, -ian and –ship. Verb (7 words) with affixes such as be-, ful-, pre-, re- and up-. Adjective (3 words) with affixes such as im- , -y and –eous.